PENGEMBANGAN TES HASIL BELAJAR MATEMATIKA DAN MOTIVASI BELAJAR MATEMATIKA PADA MATERI SIFAT - SIFAT BANGUN DATAR DI KELAS 4 - Rosatria Rahmatika; Muh. Nana Suptiatna; Istiqomah Eka Diyanti; Yuyu Yuhana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The researcher aims to develop HOTS test instruments that can evoke the problem-solving process in mathematics subjects on the material of the properties of flat shapes. The method used in this research is the development research method (R&D) which is a process or steps to develop a new product or improve existing products. This research uses quantitative question analysis. Quantitative question analysis with validity test according to 3 experts on mathematics cognitive ability test using Aiken formula test. Furthermore, the interrater reliability test was carried out on the question using the Ebel formula (1951), the formula given by Ebel was used to estimate the reliability of the assessment results of k assessors on n subjects, followed by analysis of the test items to determine the level of difficulty of the items, differentiating power, and the effectiveness of the checkers with the formula. Then the empirical validation test is carried out by calculating the correlation coefficient between the total score of the question and the score of each item. The formula used to calculate this correlation is shown by the product moment correlation formula. Furthermore, it is tested with reliability with the Cronbach's Alpha formula. Cronbach's Alpha is a measure of reliability that has a value ranging from zero to one the results of expert theoretical validation of the mathematics cognitive ability test obtained a score of 0.87 including in the good category, while the Interrater reliability test results show a score of 0.53 which is interpreted as a moderate coefficient. calculation of the level of difficulty there are four questions in the medium category, ten questions are in the high category one question is in the high category. The results of empirical validity calculate reliability using the Cronbach Alpha formula obtained a number 0.91 interpreted according to Guilford the value of r = 0.91 including very high criteria.